Pengaruh Gaya Kepemimpinan dan Disiplin Kerja Terhadap Kinerja Karyawan pada PT. Wita Kharisma Jaya Bersama Jawa Barat - Kristina Oren Lanan; Aden Prawiro Sudarso (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This research aims to determine the influence of Leadership style and Work Discipline on Employee Performance at PT. Wita Kharisma Jaya Bersama Bekasi West Java. The method used is a quantitative method with a descriptive approach. The sampling technique used was Non Probability sampling with a sample of 65 respondents. In collecting data using observation techniques and distributing questionnaires. Data analysis uses validity tests, reliability tests, classical assumption tests, regression analysis, correlation coefficient analysis, coefficient of determination analysis, and hypothesis testing. The results of this research are that leadership style has a significant effect on employee performance with the regression equation Y = 10,933 + 0.744 X1. The correlation coefficient value for the Leadership style variable is 0.829, meaning that the two variables have a very strong level of relationship with a coefficient of determination of 68.7%. Hypothesis testing obtained a value of tcount > ttable or (11.751 > 0.244). Thus Ho1 is rejected and Ha1 is accepted. This means that there is a significant influence between Leadership style and Employee Performance. Work Discipline has a significant effect on Employee Performance with the regression equation Y = 5.933 + 0.841 X2. The Work Discipline correlation coefficient value is 0.878, meaning that the two variables have a very strong level of relationship with a coefficient of determination of 77.1%. Hypothesis testing obtained a value of tcount > ttable or (14.549 > 0.244). Thus, H02 is rejected and Ha2 is accepted, meaning that there is a significant influence between Work Discipline on Employee Performance. Leadership style and Work Discipline have a significant effect on employee performance with the regression equation Y= 4.939 + 0.291 X1 + 0.583 X2. The correlation coefficient value is 0.897, meaning that the independent variable and the related variables have a very strong level of relationship with a coefficient of determination of 80.4%. Hypothesis testing obtained a value of fcount > ftable or (127.119 > 3.14). Thus, Ho3 is rejected and Ha3 is accepted, meaning that there is a significant simultaneous influence between Leadership style and Work Discipline on Employee Performance at PT. Wita Kharisma Jaya Bersama Bekasi West Java.